The Relationship Of The Level Of Mother's Knowledge With The Risk Of Closed Pregnancy In Soa Senayu Village - Theresia Serlin Anameha,; Retno Palupi Yonni Siwi,; Erma Retnaningtyas,; Nita Dwi Astikasari, (Journal of Health Science Community, 2024)
Background:The risk of pregnancy is a pregnancy where the life and health of the mother and baby can be threatened, one of which is caused by a pregnancy that is too close. If a pregnant mother has more knowledge about the high risks of pregnancy, it is likely that the mother will think about preventing, avoiding or overcoming the problem of the risks of pregnancy, and the mother will have the awareness to have her pregnancy checked. Objective:mI knowThe Relationship between Maternal Knowledge Level and the Risk of Close Pregnancy. Research Method:The type of research used in this research is an analytical survey with a cross-sectional study approach. The independent variable is the mother's level of knowledge. The dependent variable is the risk of close pregnancy spacing in Soa Senayu Village.The data was processed using the SPSS program using statistical testschi squarewith a degree of significance (α) of 0.05. Results:The results of the research showed that respondents who had a high level of knowledge distribution had a risk of pregnancy that was not at risk, as many as 11 (68.4%), and a distribution of low levels of maternal knowledge with a pregnancy that could be at risk was 13 people (68.4%). . the results of the statistical test using Chi-Square, obtained a result of 0 cells (0%), so using the Continuity Correction alternative the value obtained was ρ= 0.064 where ρ < α (0.05). Conclusions and recommendations:There isThe relationship between the level of knowledge and the risk of pregnancy spacing. It is hoped that this research can become a source of information and knowledge that can increase pregnant women's knowledge about the risks of pregnancy spacing and the dangers they cause.